(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The kinematics singularity of a manipulator is a central problem in robot control and trajectory tracking since the jacobian matrix rank is decreased. The robot in this paper consists of three links with revolute joints and spherical wrist (six degree of freedom). Danivat Hartenberg convention is used to predicate the forward kinematics position and orientation of the robot end effector. Both geometrical and analytical jacobian are presented to identify and analyze the robot singularities in order to avoid them in trajectory planning and control problems. The investigation shows that the manipulator has three type of singularity (elbow singularity when θ3=0,π, Shoulder singularity occurs at the condition and Wrist singularity when θ5=0,π).The calculated singular configurations have been verified and simulated with Peter Corke robotics toolbox of MATLAB. The presented approaches can be applied to analyze the singularity of other similar kinds of robot manipulators in order to achieve a suitable solution for tracking trajectories.